Identification of SUMO Targets by a Novel Proteomic Approach in Plants1. Issue 1 (21st January 2013) - López‐Torrejón, Gema; Guerra, Davide; Catalá, Rafael; Salinas, Julio; del Pozo, Juan C.
Abstract: Post‐translational modifications (PTMs) chemically and physically alter the properties of proteins, including their folding, subcellular localization, stability, activity, and consequently their function. In spite of their relevance, studies on PTMs in plants are still limited. Small Ubiquitin‐like Modifier (SUMO) modification regulates several biological processes by affecting protein‐protein interactions, or changing the subcellular localizations of the target proteins. Here, we describe a novel proteomic approach to identify SUMO targets that combines 2‐D liquid chromatography, immunodetection, and mass spectrometry (MS) analyses. We have applied this approach to identify nuclear SUMO targets in response to heat shock. Using a bacterial SUMOylation system, we validated that some of the targets identified here are, in fact, labeled with SUMO1. Interestingly, we found that GIGANTEA (GI), a photoperiodic‐pathway protein, is modified with SUMO in response to heat shock both in vitro and in vivo .